APLIKASI SISTEM PENUNJANG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI DI SMP NEGERI - 8 PALANGKA RAYA - Jadiaman Parhusip; Enny D O; Thabut Rachmani Jekwoso (IIB Darmajaya, 2017)
The criteria which used to recommend the outstanding students of SMPN-8 Palangka Raya are not compatible with the applied regulations. Therefore, this research aims to help the principal of SMPN-8 Palangka Raya to decide which students have to choose according to the applied regulations.The Decision Support System in deciding the outstanding students of SMPN-8 Palangka Raya is constructed by Analytical Hierarchy Process method. This system also uses Waterfall method to develop the software with some phases which are problem identification, design of the system, implementation and test of the system. This Decision Support System processes data which is related to data management of user, criteria of data , data management of students, the decision support system on deciding students and print out reports. This system gives information about rank of students to help the principal of SMPN-8 Palangka Raya to make decision to choose the outstanding students. This system has been tested by Blackbox Testing. Based on the result, these data applications are able to give the same result with the manual counting in MS Excel. The final score is 7.1 which are stated as Grade A (very proper). Thus, the result on the application is alike with the manual calculation on the MS Excel. Keyword : Decision Support System, Analytical Hierarchy Process, Junior High School, Student achievement